Standardization of skin cleansing in vivo: part II, validation of a newly developed Automated Cleansing Device (ACiD) - Sonsmann, Flora Karla; Strunk, M.; Gediga, K.; Schliemann, Sibylle; Seyfarth, Florian; Elsner, Peter; Diepgen, Thomas L.; Kutz, G.; John, Swen Malte (Skin research & technology, 2014)
Background Skin cleansers for occupational use are manufactured for different types and degrees of soiling without common, legally binding requirements for product testing. This leads to different, manufacturer-specific test methods and a lack of comparable information on skin cleansing products. Objectives The aim of this investigation was to validate a newly developed standardized automated cleansing device (ACiD) for in vivo evaluation of industrial skin cleansers. Methods Two ACiD were tested regarding the intra- and inter-device specific reproducibility of test results. Results Skin cleansing process carried out by the three independent washing modules which constitute an ACiD-unit and two separate ACiD-units led to highly comparable results. There was no significant difference between the washing modules or between the two separate ACiD-units detected. Only different parameter settings resulted in significantly different detergency. Conclusions Intra- and inter-device specific test results of an in vivo model of skin cleansing using the automated cleansing device (ACiD) were reproducible. The long-term aim is a standardized classification of occupational skin cleansing products comparing their skin cleansing effectiveness in relation to their skin irritancy. This might then provide the basis for a rational specific product selection by consumers and may be used as a tool for future product development by manufacturers.